Pharmaceutical Pricing and Reimbursement Policies in Slovakia - Kaló, Zoltán (OECD Health Working Papers, 2008)
This paper examines aspects of the policy environment and market characteristics of Slovakia's pharmaceutical sector, and assesses the degree to which Slovakia has achieved certain policy goals. Pharmaceutical expenditure in Slovakia accounts for a higher share of total health expenditure than it does in any other OECD country, and the share of national income going to pharmaceuticals is exceeded only in Hungary. Although its relatively low national income is a partial explanation for Slovakia's status in this respect, this review finds that Slovakia has scope to reduce its expenditures and the rapid rate of growth in its pharmaceutical spending. Financing of pharmaceutical expenditure in Slovakia rests more heavily on the public sector than is typical in the OECD, with out-of-pocket spending accounting for just a quarter of total expenditure. The effectiveness of international price referencing in limiting Slovak prices for on-patent pharmaceutical products is questionable. For products that have gone off-patent and for those with similar chemical structure, a reference-pricing scheme and competition among generic alternatives results in effective price control, although incentives for generic substitution are weak (for patients) and misaligned (for pharmacists). When deciding whether a drug will be reimbursed through the social insurance scheme, the cost-effectiveness of new pharmaceuticals is not assessed. On the other hand, certain policy goals have been achieved. The accessibility and availability of medicines--including the most innovative products--is good; affordability is supported by relatively low average co-payment levels. While more expensive drugs usually have higher cost-sharing, drugs are not excluded from coverage on affordability grounds